Foraging Payoffs Change With Group Size in Kin and Non-kin Groups of an Argyrodinae Kleptoparasitic Spider, Argyrodes miniaceus - Yu, Chia-Ning; Kuo, Chi-Yun; Lin, Hsing-Chieh; Su, Yong-Chao (Frontiers in Ecology and Evolution, 2022)
Abstract Evolutionary transitions from solitary to group-living are ubiquitous in animal systems. While the fitness consequences of group size changes are often investigated, the long-standing debate on whether kinship is a prerequisite of sociality is still ongoing. In the current study, we used kleptoparasitic spiders Argyrodes miniaceus (subfamily Argyrodinae, Theridiidae) as a model system to assess the role of group size on the foraging payoffs of kin and non-kin groups. We set up laboratory-manipulated kin and non-kin foraging groups and used feeding occurrence and duration as proxies for foraging benefits and feeding latency and the number of host attacks as estimates of foraging costs. Compared to solitary individuals, feeding durations of successfully fed individuals in groups was not significantly different from that of solitary foragers in both kin and non-kin groups. The occurrences of feeding decreased significantly in group sizes two and above, in non-kin groups, and in group sizes three and above, in kin groups. In kin groups, groups size two had significantly shorter feeding latencies compared to other group sizes, even though feeding duration did not change systematically with group size. Similarly, the number of attacks from the hosts were highest in non-kin groups with more than two individuals and in kin groups with more than three individuals. The juxtaposition of kin and non-kin group showed that A. miniaceus enjoyed the highest foraging payoffs when being solitary or in small groups (group size two). However, host attacks appeared to hamper feeding occurrences in kin groups, which was not observed in non-kin groups. Our results contrast sharply with the feeding benefits of kinship recorded in kin-based groups of sub-social species present in related subfamilies in the Theridiidae.